Interest Rate and Financial Performance of Listed Deposit Money Banks in Nigeria - Oluwayemisi, Ali-Momoh Betty; Fajuyagbe, Bamikole Samson (The Journal of Accounting and Management, 2022)
The study examined a relationship between interest rates and the financial performance of listed deposit money banks in Nigeria. Specifically, the study investigated how the growth of domestic money supply affect financial performance; how the maximum bank lending rate affect financial performance; how the monetary policy rate influences the financial performance of Nigerian deposit money banks; and how the rate of inflation affects the financial performance of Nigerian deposit money banks. The study made use of secondary data. The study’s design comprised both descriptive and ex-post facto analyses. The analysis was carried out using panel data. The statistical analysis revealed that there are positive and statistically significant relationships between domestic money supply and financial performance; maximum lending rate has a positive relationship with financial performance; the relationship between the two is statistically significant; monetary policy rate has a positive and statistically significant effect on financial performance; and inflation has a negative and statistically significant effect on financial performance. The study concluded that, interest rate liberalization in Nigeria benefited the financial performance of the country's deposit money banks. It further concluded that, effective interest rate administration has played a critical role in the growth and development of Nigeria's deposit money banks. This suggests that a change in the money supply have a major effect on the financial performance of listed deposit money banks in Nigeria. As a consequence, the study proposed that the Central Bank of Nigeria redefine domestic money supply as a monetary policy instrument by defining an equilibrium level. This would make additional cash accessible to deposit money institutions, allowing them to enhance their performance and accelerate loan applications.